System identification of a concrete arch dam and calibration of its finite element model. - Alves, S.W (Earthquake engineering & structural dynamics.)
A magnitude 4.3 earthquake occurred near Pacoima Dam on 13 January 2001. An accelerometer array that had been upgraded after the Northridge earthquake recorded the motion with 17 channels on the dam and the dam?foundation interface. Using this data, properties of the first two modes are found from a system identification study. Modal properties are also determined from a forced vibration experiment performed in 2002 and indicate a significantly stiffer system than is estimated from the 2001 earthquake records. The 2001 earthquake, although small, must have induced temporary nonlinearity. This has implications for structural health monitoring. The source of the nonlinear behaviour is believed to be loss of stiffness in the foundation rock. A finite element model of Pacoima Dam is constructed and calibrated to match modal properties determined from the system identification study. A dynamic simulation of the 2001 earthquake response produces computed motions that agree fairly well with the recorded ones.